Problem Based Learning Modules in Environmental Education to Improve Problem Solving Ability - Ramandani, Risqilia; Lestari, Nurita Apridiana; Budiarto, Eko; Uulaa, Rizki Fitri Rahima (International Journal of Research and Community Empowerment, 2024)
Problem solving is the ability of groups and individuals to find a solution to a problem. It is necessary to have problem-solving skills to face the challenges of the 21st century. Problem-solving abilities can be improved using the problem-based learning model. The use of the environment as a learning resource makes learning more meaningful. So it is necessary to develop teaching modules based on problem-based learning integrated with environmental education to improve problem-solving skills. This study aims to analyze the results of the validity of teaching modules based on problem-based learning integrated with environmental education to improve problem-solving skills on climate change material. The method used in this study is the R&D method with the ADDIE development model. In this study, there were three stages used, namely the analysis stage, namely determining the needs of students regarding the teaching modules on climate change material, the design stage, namely planning the teaching modules to be developed, and the development stage, namely compiling and validating. The validity of the teaching module is assessed based on the feasibility of the content, language and presentation which consists of nine indicators. The analysis technique was carried out by calculating the results of the teaching module validity of the 4 validators. The advantages of this teaching module are that it uses the PBL learning model, integrates environmental education, trains indicators of problem-solving abilities. The drawback is that the teaching modules are not yet digital based. The main suggestion from the validator is to make the cover page more attractive and characterize the author's character and the trigger questions included at the problem orientation stage can be broader (not short). The results showed that the average validity value of the three validators in problem-based learning integrated teaching modules integrated with environmental education to improve problem-solving skills on climate change material developed had very valid validity results. This is in accordance with the overall average value of validity and reliability obtained by 96.53% and 93.65%.  So it can be concluded that the teaching modules developed are feasible to be applied in the learning process. The implication of this research is to have a positive impact on students regarding the use of environmental education (environment as a learning resource) in physics learning so that it can be used as a solution to improve students' problem-solving abilities.